2023
DOI: 10.1097/js9.0000000000000270
|View full text |Cite
|
Sign up to set email alerts
|

Regional analgesia techniques for lumbar spine surgery: a frequentist network meta-analysis

Abstract: Background: Various regional analgesia techniques are used to reduce postoperative pain in patients undergoing lumbar spine surgery. Traditionally, wound infiltration (WI) with local anesthetics has been widely used by surgeons. Recently, other regional analgesia techniques, such as the erector spinae plane block (ESPB) and thoracolumbar interfascial plane (TLIP) block, are being used for multimodal analgesia. The authors aimed to determine the relative efficacy of these using a network meta-analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…In some spine surgery studies, it has been shown to be effective, 70,71 but a definite conclusion cannot be drawn due to heterogeneity and a lack of robust data 72 . In recent studies, PNBs have outshone LA infiltration in this matter 73,74 . In addition, similar to epidural catheters, surgeons are able to insert PVB or ESP catheters directly between desired muscles toward the end of surgery, reducing the risk of surgical damage as these are placed under direct visualization 44,53 .…”
Section: Enhanced Recovery After Surgery and Multimodal Analgesiamentioning
confidence: 99%
See 2 more Smart Citations
“…In some spine surgery studies, it has been shown to be effective, 70,71 but a definite conclusion cannot be drawn due to heterogeneity and a lack of robust data 72 . In recent studies, PNBs have outshone LA infiltration in this matter 73,74 . In addition, similar to epidural catheters, surgeons are able to insert PVB or ESP catheters directly between desired muscles toward the end of surgery, reducing the risk of surgical damage as these are placed under direct visualization 44,53 .…”
Section: Enhanced Recovery After Surgery and Multimodal Analgesiamentioning
confidence: 99%
“…72 In recent studies, PNBs have outshone LA infiltration in this matter. 73,74 In addition, similar to epidural catheters, surgeons are able to insert PVB or ESP catheters directly between desired muscles toward the end of surgery, reducing the risk of surgical damage as these are placed under direct visualization. 44,53 See Table 1 for comparisons of neuraxial and PNB techniques in the adult and pediatric population.…”
Section: Surgical Infiltration: Analgesia By Surgeon Versus Anesthesi...mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the recent article by Hong et al . 1 . The authors performed an interesting network meta-analysis that evaluated the postoperative analgesic efficacy of erector spinae plane block (ESPB), thoracolumbar interfascial plane (TLIP) block, wound infiltration (WI), and controls.…”
mentioning
confidence: 99%
“…Third, the questionable clinical significance was further biased by using nonopioid multimodal analgesia, which may attenuate perceived pain and mask a possible effect of the intervention 1 . Perioperative administration of other analgesics, such as paracetamol (acetaminophen) and non-steroidal anti-inflammatory drugs (NSAIDs), was also not considered in the analyses, which led to further doubt about the robustness of results.…”
mentioning
confidence: 99%